CONCRETIZATIONOF URGENT REASON AND SUFFICIENTEVIDENCE IN PROVIDING MARRIAGE DISPENSATION FOR CHILDREN BY THE JUDGE - Mansari, Mansari; Fatahillah, Zahrul; Muzakir, Muzakir; Oslami, Ahmad Fikri; Zainuddin, Muslim (Nurani, 2020)
The article discusses the concretization of urgent reasons and sufficient evidence for granting marriage dispensations in Law Number 16 Year 2019. This purpose of this study is how to concretize urgent reasons and sufficient evidence by the judge inproviding marriage dispensations for children. Researchers used empirical legal research methods and primary legal materials, secondary legal materials and primary data obtained through interviews with Syar’iyah court judges. Data analysis was performed prescriptively to provide an assessment of the implementation of the Marriage Law. The results showed that the petition for marriage dispensation for children after the legitimation of Law Number 16 Year 2019 increased despite being complicated by the Supreme Court Regulations and it was resulted that the age of the petitionfor marriage dispensation between 15 and 19 years old. Children must attend the court for obtaining the advice related to the risk of child marriage. Concretization of the urgent condition and sufficient evidence is carried out with observing the facts at thecouncil, namely worrying about acts that are prohibited from religion, getting pregnant out of wedlock and doing tandem (khalwat). The sufficient evidences were concreted by the judge. He/She requested the witnesses who knew the background of the parents and prospective husband/ wife attended the council to investigate the reasons for the marriage of the child and proof of marriage rejection from the KUA, Child Identity Cards, birth certificates and final diplomas. It is recommended that judges must prioritize the best interestfor the children and the reproductive health certificate from the hospital should be requested.